The Physico-Chemical and Microbial Content of White Cheese Obtained Using Plant-based, Animal and Microbial Enzymes - Pelin Ertürkmen; Sinan Akbal; Zerrin Arısoy (Turkish Journal of Agriculture: Food Science and Technology)
It is required to increase the amount of coagulant enzyme substitutes obtained from various sources that are equivalent to animal rennet in order to meet the rising demand for cheese. This study looked into the availability of plant-based enzymes as an alternative to rennet made from animals and microorganisms, which are frequently employed in the manufacturing of white cheese. Using animal (100% chymosin), microbial (obtained from Muchor miehei), and plant-based (Safflower seed, 80% chymosin-20 percent pepsin, purified from Cartamus tinctorius L.) enzymes, 6 varieties of raw and pasteurized milk cheese were made for this purpose. The values of SH, ripening index, water-soluble nitrogen (WSN), nitrogen dissolved in trichloroacetic acid (TCA), and yeast-mold increased after storage in cheeses made with various coagulant enzymes. During storage, the values for dry matter, pH, protein, Total Aerobic Mesophilic Bacteria (TAMB), lactobacilli, lactococci and coliforms all reduced. In terms of L*, a* and b* values, different rennet usage was discovered to be significant among cheese samples. The casein protein began to hydrolyze and the strength of the bands decreased in SDS-PAGE with the breakdown of the αs-casein and β-casein fractions on the 90th day of maturation in P1 and P4 numbered cheeses, which used plant-based enzyme made from raw and pasteurized milk. These changes in casein fractions resulted in a bitter taste in cheese made with plant-based enzymes. The use of plant-based enzymes in the manufacturing of white cheese was shown to produce results that were comparable to those of animal and microbial enzymes and did not have any negative effects on the cheese's physicochemical and microbiological quality parameters. When making fresh white cheese, the plant-based enzyme extracted from Carthamus tinctorius L. can be employed as a promising source of plant coagulants.